LITERATURE REVIEW: INFLUNCING FACTORS OF QUALITY OF LIFE OF MENOPAUSE WOMEN - Marni Marni; Domingos Soares; Siti Farida; Elfia Riandani; Erlina Erlina (LPPM Universitas Duta Bangsa Surakarta, 2022)
Introduction : An elderly woman will experience menopause. This condition must immediately get good treatment so that the quality of life of these women is good or improved. For this reason, it is necessary to know the factors that affect the quality of life of post-menopausal women. Objectives: The purpose of this study was to determine the factors that affect the quality of life of postmenopausal women. Method: Literature Review, by searching the Pubmed, ProQuest, Science Direct and Google scholar databases. Obtained 7 articles to be included in the review. Results: The factors that affect the quality of life of postmenopausal women are the use of hormonal supplements in the form of phytoestrogens, active in sexual activity, physical exercise, class activities and counseling. Conclusion: Good sexual activity will improve the quality of life of postmenopausal women, in addition to attending counseling classes, adding phytoestrogen supplements and using lubricants or liquid lubricants to prevent infection..